The effect of MEP pathway and other inhibitors on the intracellular localization of a plasma membrane-targeted, isoprenylable GFP reporter protein in tobacco BY-2 cells [v2; ref status: indexed, http://f1000r.es/2af] - Michael Hartmann; Andrea Hemmerlin; Elisabet Gas-Pascual; Esther Gerber; Denis Tritsch; Michel Rohmer; Thomas J Bach (F1000Research, 2013)
We have established an in vivo visualization system for the geranylgeranylation of proteins in a stably transformed tobacco BY-2 cell line, based on the expression of a dexamethasone-inducible GFP fused to the carboxy-terminal basic domain of the rice calmodulin CaM61, which naturally bears a CaaL geranylgeranylation motif (GFP-BD-CVIL). By using pathway-specific inhibitors it was demonstrated that inhibition of the methylerythritol phosphate (MEP) pathway with known inhibitors like oxoclomazone and fosmidomycin, as well as inhibition of the protein geranylgeranyltransferase type 1 (PGGT-1), shifted the localization of the GFP-BD-CVIL protein from the membrane to the nucleus. In contrast, the inhibition of the mevalonate (MVA) pathway with mevinolin did not affect the localization. During the present work, this test system has been used to examine the effect of newly designed inhibitors of the MEP pathway and inhibitors of sterol biosynthesis such as squalestatin, terbinafine and Ro48-8071. In addition, we also studied the impact of different post-prenylation inhibitors or those suspected to affect the transport of proteins to the plasma membrane on the localization of the geranylgeranylable fusion protein GFP-BD-CVIL.